skills approach in the construction professional profile of Agricultural TSU UCLA (Revista Electrónica REDINE, 2018)
The professional competency profile is the document that describes the functions that identify a particular professional, specifies the responsibilities of each function and the elements associated with these, from an analysis of the essential tasks that result from decomposition. The objective is to build the professional profile approach based on the farming higher Technician of University Centroccidental "Lisandro Alvarado". This work is presented in the form of educational experience. The study was conducted using functional analysis, which is part of qualitative research. Workshops were held for the design of the proposal which resulted in the professional profile of a technician, effective, on time use and academic resources, material and financial, and based on the education model of UCLA. A new professional profile, produce benefits related to production efficiency and improved quality of life and work for all members of the institution.
Keywords: competence; professional profile; agricultural technician